2011
DOI: 10.1093/ndt/gfq758
|View full text |Cite
|
Sign up to set email alerts
|

TLR-4+ peripheral blood monocytes and cardiovascular events in patients with chronic kidney disease--a prospective follow-up study

Abstract: Unexpectedly, we could not detect an association between CD14+/TLR-4+ monocytes and incident CVE as well as CV death in stable hemodialysis patients. Further studies have to clarify the potential role of this cell population for CV outcome in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…With that in mind, the short lifespan of neutrophils makes the cells the best target for measuring acute and short time stimuli such as the direct effect of a single haemodialysis. Despite the fact that the number of monocytes expressing TLR/CD14 positively correlates with a high sensitivity CRP concentration (proving the prevailing inflammatory state in the haemodialysed patients [ 26 ]), we observed no significant changes in TLR4 expression on neutrophils forming the biggest population of carriers of the pro-inflammatory alarmins [ 11 ].…”
Section: Discussionmentioning
confidence: 93%
“…With that in mind, the short lifespan of neutrophils makes the cells the best target for measuring acute and short time stimuli such as the direct effect of a single haemodialysis. Despite the fact that the number of monocytes expressing TLR/CD14 positively correlates with a high sensitivity CRP concentration (proving the prevailing inflammatory state in the haemodialysed patients [ 26 ]), we observed no significant changes in TLR4 expression on neutrophils forming the biggest population of carriers of the pro-inflammatory alarmins [ 11 ].…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, in a separate study, TLR4 expression in peripheral blood monocytes was evaluated in 191 patients with ESRD. 25 TLR4 expression correlated significantly with age (r = 0.2, p = 0.007), CRP (r = 0.2, p = 0.008), and mean arterial blood pressure (r = −0.2, p = 0.02).…”
Section: Discussionmentioning
confidence: 97%
“…A recent study by Lorenzen et al [10] indicated that several traditional risk factors did not affect incident cardiovascular events including death in hemodialysis patients. Therefore, other factors, including free light chains, may be more important for the survival of hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%